An Inventory Problem with Discrete Time Review and Replenishment by Batches of Fixed Size - Resh, M.; Naor, P. (Management Science, 1963)
An inventory system under periodic review is considered. If at the time of review the stock has fallen below a given level, L, a fixed quantity, Q, is ordered; otherwise no action is taken. It is assumed that delivery time is negligible. Two costs are considered to be of importance: one proportional to the average overage, the second proportional to the average shortage. Under exponential demand assumptions optimal values of L and Q are obtained.